Workshop Inovasi Digital: Penerapan Ilmu Komputer dalam Metode Pengajaran Al-Qur’an pada STAI Nusantara - Rahmi Hajriyanti; Ismail; Fauzan Putraga al bahri; Syamsul Rizal (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2025)
Advances in information technology have opened up great opportunities for innovation in learning, including in the teaching of the Qur'an. However, many teachers in religious educational institutions do not yet have adequate skills in utilising digital technology. This community service activity aims to improve the digital literacy and technical skills of lecturers, ustaz, and students at STAI Nusantara in applying computer science to Qur'an teaching methods. The implementation methods include interactive lectures, hands-on training, learning simulations, and post-workshop mentoring. The results of the activity show a significant improvement in participants' abilities to create multimedia-based learning media, utilise tahsin-tahfidz applications, and manage online classes. This activity is expected to be the first step towards adaptive Qur'anic education that keeps pace with technological developments without abandoning the strengths of traditional methods.